Pengaruh Pengetahuan Kewirausahaan, Motivasi Berwirausaha dan Lingkungan Keluarga Terhadap Minat Berwirausaha Mahasiswa Akuntansi Universitas Islam Malang dan Universitas Islam Negeri Maulana Malik Ibrahim Malang - Rifaldi, Mochammad; Sudaryanti, Dwiyani; Junaidi, Junaidi (Universitas Islam Malang, 2024)
This research was conducted to determine the influence of entrepreneurial knowledge, entrepreneurial motivation and family environment on entrepreneurial interest. The population in the research were students from the Faculty of Economics and Business, Accounting Study Program, Islamic University of Malang, and Maulana Malik Ibrahim State Islamic University class of 2019 and 2020, the exact number of which is not yet known. The approach method uses a non-probability sampling technique, namely purposive sampling, namely a sample collection technique based on certain criteria using a questionnaire distributed to 75 respondents and using the SPSS analysis tool. The research results show that entrepreneurial knowledge, entrepreneurial motivation and family environment simultaneously influence entrepreneurial interest and partially entrepreneurial knowledge, entrepreneurial motivation and family environment influence entrepreneurial interest.Keywords: Entrepreneurial knowledge, entrepreneurial motivation, family environment, entrepreneurial interest